2011
DOI: 10.1007/s12663-010-0097-5
|View full text |Cite
|
Sign up to set email alerts
|

Verruca Vulgaris of the Tongue

Abstract: The viral warts also known as verruca vulgaris are caused by papova group of viruses. Such warts are commonly seen on the skin but occasionally may appear in the oral cavity. There are three types of warts namely verruca plana; verruca vulgaris and filiform. The incubation period of such warts varies from 6 weeks to a year. The warts spread by autoinoculation and seldom show koebner phenomenon. The majority of mucosal warts are seen in those children who also have warts on hands. In such cases the virus may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…2,4,15 A single case of verruca vulgaris in the tongue was found in the present study, whereas only two cases have been reported in the literature involving this site. 16,17 Although keratoacanthoma occurs in all age groups, the majority of cases have been reported to occur over the age of 40 year, with a male predilection. 18 A single case of keratoacanthoma was found in this analysis, affecting a 13-year-old female patient, which is quite uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,15 A single case of verruca vulgaris in the tongue was found in the present study, whereas only two cases have been reported in the literature involving this site. 16,17 Although keratoacanthoma occurs in all age groups, the majority of cases have been reported to occur over the age of 40 year, with a male predilection. 18 A single case of keratoacanthoma was found in this analysis, affecting a 13-year-old female patient, which is quite uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it appears as a single, asymptomatic, pedunculated or sessile, soft to firm mass with verrucous, granular, or papillomatous surface ( Figure 17 ). The lesion may be white, slightly red, or normal in color [ 4 , 68 70 ]. Papilloma usually enlarges rapidly to a maximum size of 5 mm with little or no change in diameter thereafter [ 10 ].…”
Section: Lesions With Smooth Surfacementioning
confidence: 99%
“…The incidence has increased considerably due to the changes in sexual behaviour and an increase in the practice of oral sex [11]. In contrast, oral verruca vulgaris lesions caused by HPV types 1, 2, 4, 7 as in the current case are rarer with one reported case of VV of the tongue [12]. The lesions are usually caused by autoinoculation from lesions on the fingers and hands mainly in the children [13].…”
Section: Discussionmentioning
confidence: 88%